Gamma-ray irradiation modulates PGRMC1 expression and the number of CD56+ and FoxP3+ cells in the tumor microenvironment of endometrial endometrioid adenocarcinoma - Zinovkin, Dmitry Aleksandrovich; Lyzikova, Yulia Anatolievna; Nadyrov, Eldar Arkadievich; Petrenyov, Daniil Rudolfovich; Yuzugulen, Jale; Pranjol, Md Zahidul Islam (Korean Soc Therapeutic Radiology & Oncology, 2021)
Purpose: Although the conventional gamma ray brachytherapy has been successful in treating endometrioid endometrial adenocarcinoma (EC), the molecular and cellular mechanisms of this anti-tumorigenic response remain unclear. Therefore, we investigated whether gamma ray irradiation induces changes in the number of FoxP3(+) T-regulatory lymphocytes (Tregs), CD56(+) natural killer cells (NK), and the expression of progesterone receptor membrane component 1 (PGRMC1) in the tumor microenvironment (TME). Materials and Methods: According to the inclusion criteria, 127 cases were selected and grouped into irradiation-treated (Rad(+)) and control (underwent surgery) groups and analyzed using immunohistochemistry. Predictive prognostic values were analyzed using Mann-Whitney U test, ROC analysis, relative risk, log-rank, Spearman rank tests and multivariate Cox's regression. Results: We observed significant differences (p < 0.001) between the radiation-treated patients and the control groups in FoxP3(+) Tregs numbers, CD56(+) NK cells and PGRMC1 expression. Gamma ray induced a 3.71- and 3.39-fold increase in the infiltration of FoxP3(+) cells, CD56(+) NK cells, respectively and 0.0034-fold change in PGRMC1 expression. Univariate and multivariate analyses revealed predictive role of the parameters. In the irradiated patients' group, inverted correlations between clinical unfavorable outcome, FoxP3(+) Tregs and CD56(+) NK cells were observed. Conclusion: Our results suggest an immune-modulating role, specifically by increasing immune cell infiltration, of gamma radiation in the TME which may potentially be utilized as biomarkers in prognostic values.
Keywords: Gamma rays; CD56; FoxP3; PGRMC1; Tumor microenvironment; Endometrioid endometrial carcinoma